Plant Remains from Burzahom, Kashmir - Purkayastha, S. K.; Lal, B. (Indian Forester, 1976)
The plant remains excavated from the Neolithic site Burzahom (circa 1535 B.C. to circa 2375 B.C.) is Kashmir showed that the "burnt material of ceiling" consisted mostly charred twigs of Parrotiopsis and Prunus. The bark Hakes found in them probably belong to Prunus sp. The plant remains also include a number of samples of deteriorated wood samples of Myricaria sp. which probably date back to 4th century A.D. There is no evidence to support the view that the area abounded in birch (Betula sp.) as the name of the place would indicate.